2013
DOI: 10.1172/jci65871
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-374a activates Wnt/β-catenin signaling to promote breast cancer metastasis

Abstract: Tumor metastasis involves a series of biological steps during which the tumor cells acquire the ability to invade surrounding tissues and survive outside the original tumor site. During the early stages, the cancer cells undergo an epithelial-mesenchymal transition (EMT). Wnt/β-catenin signaling is known to drive EMT and metastasis. Here we report that Wnt/β-catenin signaling is hyperactivated in metastatic breast cancer cells that express microRNA 374a (miR-374a). In breast cancer cell lines, ectopic overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
288
5
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(308 citation statements)
references
References 56 publications
12
288
5
3
Order By: Relevance
“…Wnt signalling pathway has been shown to control self-renewal and differentiation of cancer cells 29 , and aberrant activation of Wnt signalling leads to EMT in breast epithelial cells 41,42 . As a receptor for the Wnt pathway, FZD10 is expressed at high level in colorectal cancers, gastric cancers, as well as in synovial sarcomas, and is associated with the activation of Wnt signalling in these cancers 33,34,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signalling pathway has been shown to control self-renewal and differentiation of cancer cells 29 , and aberrant activation of Wnt signalling leads to EMT in breast epithelial cells 41,42 . As a receptor for the Wnt pathway, FZD10 is expressed at high level in colorectal cancers, gastric cancers, as well as in synovial sarcomas, and is associated with the activation of Wnt signalling in these cancers 33,34,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant regulation of miRNAs has been involved in a number of human diseases, including cancers. In tumorigenesis, miRNAs may act as tumor suppressors (5,6) or oncogenes (7,8) in different types of cancers, including esophageal cancer (9). Recent clinical findings indicated that the upregulation of miR-146b was associated with poor survival in esophageal squamous cell carcinoma (10).…”
Section: Introductionmentioning
confidence: 99%
“…miRNA profiling has shown that microRNA-374a (miR-374a) is overexpressed in many types of cancer, such as head and neck squamous cell carcinoma, follicular lymphoma, osteosarcoma and bladder urothelial carcinoma (15)(16)(17)(18). In breast cancer, miR-374a was markedly upregulated in primary tumor samples from patients with distant metastases and was considered to be associated with poor metastasis-free survival (7). In gefitinib-resistant lung cancer cells, the expression of miR-374a was high (19).…”
Section: Introductionmentioning
confidence: 99%
“…In this experiment the E-cadherin expression was up-regulated by nLQ, implicating that the EMT could be reversed by nLQ at certain extent. It is suggested that the reversal EMT induced by nLQ may inhibit cancer cell metastatic stemness potency via wnt/β-catenin pathway (Cai, et al, 2013). Almanaa TN et al indicate that the anti-stem like cell effects can be induced by phytochemical agent, curcumin, in human esophageal cancer cells (Almanaa et al, 2012), the apoptotic effect via HDAC-NF-κB cascade signaling induced by the phytochemical agent, quercetin, was studied in this experiment.…”
Section: Discussionmentioning
confidence: 88%